Hydrothermal preparation of biochar from spent coffee grounds, and its application for the removal of cadmium from coal tailings leachate - Fosso-Kankeu, E.; Weideman, R.; Moyakhe, D.; Waanders, F.B.; Le Roux, M.; Campbell, Q.P. (SAIMM, 2019)
Spent coffee grounds were transformed into biochar using a hydrothermal method. Some of the biochar product was pre-treated through surfactant impregnation with sodium dodecyl sulphate (SDS) to enhance its adsorption capacity. The non-treated(NT) and pre-treated(PT) biochars were characterized using FTIR spectroscopy and SEM-EDS analyses, which revealed that the products had the potential for adsorption of heavy metals from solution and confirmed the successful impregnation of biochar with SDS surfactant. The two adsorbents were then used for the removal of cadmium from solution and the adsorption behavior and capacity determined through adsorption isotherm, kinetic, and thermodynamic studies. It was found that the cadmium was adsorbed in several concentric layers on the surface of the adsorbents through a chemisorption mechanism. The PT biochar was identified as a superior adsorbent, with a capacity of qe = 10.67 mg/g compared to the NT biochar with qe = 4.82 mg/g. The adsorption of cadmium onto the PT biochar was further determined to be spontaneous and endothermic. It was therefore concluded that the PT biochar shows potential as an adsorbent and could be considered for implementation in the treatment of metal-polluted effluents
Keywords: Spent coffee grounds; Biochar; Surfactant impregnation; Cadmium; Coal tailings leachate; Adsorption